2019
DOI: 10.1029/2018gl081041
|View full text |Cite
|
Sign up to set email alerts
|

Wind Synoptic Activity Increases Oxygen Levels in the Tropical Pacific Ocean

Abstract: The mechanisms controlling the variability of oxygen levels in the ocean are poorly quantified. I focus here on the impact of wind synoptic variability associated with tropical convective regions and extratropical storms. Removing the wind higher frequencies of variability (2 days to 1 month) in an atmosphere reanalysis used to force an ocean model decreases wind stress by up to 20% in the tropics and 50% in the midlatitudes, weakening wind‐driven ocean circulation by 20%. Oxygen levels decrease by up to 10 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 50 publications
(63 reference statements)
3
12
0
Order By: Relevance
“…In the experiment NEMO2-30DEG1500, in complement to the isopycnal propagation of the subtropical anomaly, the deep (> 1500 m) oxygen anomaly is upwelled in the eastern equatorial (500 -1500 m) part of the basin (see Fig 4i) showing a large increase in advective terms, mostly due to an increase in vertical advection), consistent with the analysis by Duteil (2019) who showed that vertical advection is the dominant process to supply oxygen from the lower to the upper thermocline in the equatorial eastern Pacific Ocean in a similar NEMO2 configuration. This simple set of experiment shows that in climate models oxygen in the lower thermocline (500 -1500 m) ocean are partially controlled by properties of IWM that enter the tropics from higher latitudes.…”
Section: Oxygen Budget and Processessupporting
confidence: 86%
See 1 more Smart Citation
“…In the experiment NEMO2-30DEG1500, in complement to the isopycnal propagation of the subtropical anomaly, the deep (> 1500 m) oxygen anomaly is upwelled in the eastern equatorial (500 -1500 m) part of the basin (see Fig 4i) showing a large increase in advective terms, mostly due to an increase in vertical advection), consistent with the analysis by Duteil (2019) who showed that vertical advection is the dominant process to supply oxygen from the lower to the upper thermocline in the equatorial eastern Pacific Ocean in a similar NEMO2 configuration. This simple set of experiment shows that in climate models oxygen in the lower thermocline (500 -1500 m) ocean are partially controlled by properties of IWM that enter the tropics from higher latitudes.…”
Section: Oxygen Budget and Processessupporting
confidence: 86%
“…We analyze the mean state of the oxygen fields, OMZ, EICS of the following model experiments (see Table 1), which previously have been used in recent studies focusing on the understanding of the tropical oxygen levels mean state or variability: -a NEMO (Nucleus for European Modelling of the Ocean) configuration with a resolution of 2°, refined meridionally to 0.5° in the equatorial region (NEMO2). The circulation model is coupled to a simple NPZD (Nutrient Phytoplankton Zooplankton Detritus) biogeochemical model that comprises 6 compartments (e.g used in Duteil et al, 2018;Duteil, 2019). The simulation has been forced by climatological forcings based on the Coordinated Reference Experiments (CORE) v2 reanalysis (Large and Yeager, 2009) and integrated for 1000 years.…”
Section: Mean Statementioning
confidence: 99%
“…Processes that are poorly represented or excluded in these simulations may cause the sensitivity of the MLD to subseasonal winds to deviate from the results reported above in the real ocean or other simulations. For example, subseasonal winds may modify Langmuir (Fan and Griffies, 2014;Li et al, 2016;Van Roekel et al, 2012) and submesoscale (Fox-Kemper et al, 2011;Thomas et al, 2013Thomas et al, , 2016, 2019 turbulence, neither of which are represented in the models used in this study. In addition, subseasonal winds modify inertial oscillations and internal waves, which are only marginally represented in the global model (see sections 2.2.2 and 2.3.2).…”
Section: Poorly Represented and Excluded Processesmentioning
confidence: 99%
“…For example, the aggregated direct impacts of subseasonal atmospheric, oceanic, and sea ice processes on subseasonal MLD variability are not well known on a global scale nor are the indirect rectified impacts of subseasonal atmospheric, oceanic, and sea ice variability on the annual mean and seasonal cycle of the MLD. In addition to building understanding of the mean and seasonal cycle of the MLD, it is necessary to understand subseasonal variability of the MLD because this variability may have important implications for biogeochemistry (Carranza et al, 2018;Carranza and Gille, 2015;Castro de la Guardia et al, 2019;Chacko, 2017;Duteil, 2019;Follows & Dutkiewicz, 2001;Fauchereau et al, 2011;Girishkumar et al, 2019;Jin et al, 2013;Lévy et al, 2009;Monteiro et al, 2015;Nicholson et al, 2016;Resplandy et al, 2009;Rodgers et al, 2014;Rumyantseva et al, 2015;Thomalla et al, 2011;Waniek, 2003;Waliser et al, 2005;Ye et al, 2013) as well as coupled atmosphere-ocean subseasonal Observations provide an important but incomplete picture of subseasonal MLD variability and its potential drivers. For example, in the atmosphere (der Van, 1957;Foltz and McPhaden, 2004;Gulev et al, 2002;Goubanova et al, 2013;Illig et al, 2014), ocean (Ferrari and Wunsch, 2009;Wunsch, 2002), and sea ice (Heil & Hibler, 2002;Kwok et al, 2003;Martini et al, 2014), subseasonal variability represents a substantial fraction of the kinetic energy near the sea surface.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CO 2 flux could be influenced by both changes in mixing and ocean circulation. Since our experiments fix the mean ocean circulation and we are able to isolate the role of NIWs on surface mixing and the resulting CO 2 flux, our study can be useful to interpret the role of the changes in the ocean circulation on the CO 2 flux if one performs similar experiments as in Duteil (2019).…”
Section: 1029/2018jc014928mentioning
confidence: 99%